How the Market Is Changing China's News: The Case of Xinhua News Agency - Xin, Xin (Lexington Books, 2012)
This book provides a critical account of the transformations, both structural and in terms of journalism practice, undergone by Xinhua, the top Party organ of the Communist regime in China, since the start of the reform age in the late 1970s. It sets out to answer a number of key questions: How far has the most influential news organization in China been marketized? How far has the marketization process changed the way in which Xinhua practices journalism? What has the impact of marketization been on Xinhua’s relationship with central, local and global actors? What does the case of Xinhua tell us about the transformation of Chinese media more generally? The book draws on a wealth of empirical data derived from a combination of documentary research at Xinhua and Reuters together with more than100 semi-structured interviews with news executives, journalists, officials and academics in Beijing, Shanghai, Guangzhou, Macau, Hong Kong and London. This book also offers: A critical review of theories of globalization, as they relate to media and communication studies, as well as Chinese studies; A discussion of the historical roots of Party journalism in China; An authoritative guide to China’s contemporary media and political environment. The book will be an invaluable reference for students and academics in communication and media studies, Chinese studies, Asian studies, international studies and development studies.